PERFORMANCE OF TELFAIRIA OCCIDENTALIS LEAF GROWN IN UREA HYDROPONIC SOLUTION (American International Journal of Agricultural Studies, 2022)
The study evaluated the performances of Telfairia occidentalis Hooker fil. under varying growth media subject to the amount of Urea granules (25 g, 50 g, 75 g, 100 g, 125 g and 150 g) dissolved in water containing micronutrients. The growth media were M25U, M50U, M75U, M100U, M125U, M150U, and Control. Two-week old seedlings of T. occidentalis raised using River-sand were transferred into the non-circulatory growth media. The growth indices (vine main length (VML), number of leaves (NL), stem girth (SG), petiole length (PL), internode (LI), leaf area (LA), and total leaf area (TLA)) of T. occidentalis were measured weekly. The root length (RL), root fresh weight (RFW), root dry weight (RDW) and pigment components were determined 5 weeks after planting following standard procedures. Across the growth media studied, the Control medium had the highest VML, NL, LA, TLA, PL and pigment composition of T. occidentalis. However, among the Urea growth media, M25U medium produced relatively the highest VML, NL, TLA, total chlorophyll, and RFW of T. occidentalis while M50U medium had the highest LA, RL and RDW. Also, T. occidentalis leaves grown in the Control medium had the highest chlorophyll content (33.22 mg/g), followed by M25U medium (22.88 mg/g) and was significantly different from the other growth media.M100U medium effectively enhanced carotenoids content (6.49 mg/g) of T. occidentalis compared to others. The study showed that the mineral composition of the growth media enhanced the performance of T. occidentalis. Hence, M25U growth media are recommended for growing T. occidentalis.JEL Classification Codes: O13.